2022
DOI: 10.3390/electronics11193162
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Behavior Identification Using Social Media Forensics

Abstract: Human needs consist of five levels, which are: physiological needs, safety needs, love needs, esteem needs and self-actualization. All these needs lead to human behavior. If the environment of a person is positive, healthy behavior is developed. However, if the environment of the person is not healthy, it can be reflected in his/her behavior. Machines are intelligent enough to mimic human intelligence by using machine learning and artificial intelligence techniques. In the modern era, people tend to post their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Supposed to be a reliable approach to anomaly detection in this field of criminal investigation. Additionally, other deep learning mechanisms, such as the DBN 25 and clustering-based methods (Ashraf et al, 2022), provide novel approaches for anomaly identification in digital forensics. Additionally, DNN 26 exist using a feature-level data fusion method (Kang HW, Kang HB, 2017) that can efficiently fuse multi-model data from several domains within related environmental contexts.…”
Section: Convergence Of Ai and Neuroprediction In Forensicsmentioning
confidence: 99%
“…Supposed to be a reliable approach to anomaly detection in this field of criminal investigation. Additionally, other deep learning mechanisms, such as the DBN 25 and clustering-based methods (Ashraf et al, 2022), provide novel approaches for anomaly identification in digital forensics. Additionally, DNN 26 exist using a feature-level data fusion method (Kang HW, Kang HB, 2017) that can efficiently fuse multi-model data from several domains within related environmental contexts.…”
Section: Convergence Of Ai and Neuroprediction In Forensicsmentioning
confidence: 99%
“…It has been suggested that a Deep Belief Network (DBN) [ 24 ] and a clustering-based methodology can provide a novel approach to anomaly identification in digital forensic data [ 25 ]. Data were collected from several channels, including electronic mail, online history, and chat logs, and the DBN was utilized to extract features from this information.…”
Section: Related Workmentioning
confidence: 99%